Immigrant home-school information flows in Finnish comprehensive schools. Issue 1 (6th March 2017) - Säävälä, Minna; Turjanmaa, Elina; Alitolppa-Niitamo, Anne
Abstract : Purpose: School is an institution that provides an opportunity to improve children's equity and wellbeing and to bridge the potential disadvantage related to ethnic- or language-minority backgrounds. Information sharing between immigrant homes and school can enhance school achievement, support positive identity formation and provide early support when needed. In this paper, the perspectives of immigrant parents, school welfare personnel and school-going adolescents are analysed in order to understand how they see their respective roles in information flows between home and school. The paper aims to discuss these issues. Design/methodology/approach: The data consist of qualitative group and individual interviews of 34 representatives of school personnel, 13 immigrant parents and 81 young people who have experienced immigration, in the metropolitan area of Helsinki, Finland. Findings: Despite general goodwill, school personnel may fail to secure the flow of information. Due to structural power imbalance, school personnel are often incapable of engaging the parents in dialogical discourse. Young people of immigrant background in turn try to manipulate the information flow in order to protect their family and ethnic group and to cope with pressures from parents. The patterns of information flows in school as a social field reproduce immigrant homes as subaltern. Adolescents act in a strategically important juncture of information flows between immigrant home and school, which indicates that home-school interaction is actually a triad. Social implications: Awareness building among school personnel is vital for equity and wellbeing of children of immigrant families. Originality/value: This triangulated analysis of patterned information flows in school as a social field provides a fresh perspective to those working with children of immigrant families.